Distribuição espaço-temporal das espécies animais envolvidas em agravos a humanos e o tratamento antirrábico em Feira de Santana, BA (2008-2019) - Nascimento, Priscylla Marcelly Vilanova Oliveira do (2022)
Domestic animals such as dogs and cats, and wild species, including bats, primates and foxes, can inflict scratches and bites on humans, favoring the transmission of zoonoses, thus causing trauma such as minor or serious injuries, mutilation and death. Among these diseases, rabies stands out, an acute viral disease with high lethality in animals and humans. The objective of this work was to investigate the epidemiological and socioeconomic factors associated with injuries to humans caused by animals, from 2008 to 2019, in the municipality of Feira de Santana, Bahia, and to characterize human anti-rabies treatment. Data from the spatial location of the neighborhoods were associated with the disease by species group, and data referring to the Human Development Index (HDI) and the unweighted Health Vulnerability Index (IVS) were obtained from the 2010 Census, being calculated for each district. The human anti-rabies care according to the prophylactic approach was associated with the epidemiological and sociodemographic characteristics of the human population affected. In the studied period, 25591 notifications were registered. There were more aggressions by carnivorous animals 4,950 (97.66%), and the dog was the most frequently involved species, representing 82.69% of notifications. Some spatial aggregates were associated with the HDI and IVS indices, but a regular distribution of them was not established. The sociodemographic profile of post-exposure care was characterized by an age range of 20 to 39 years old, male, brown, with incomplete primary education and residents of the urban area. Of the reported injuries, 75.86% did not receive treatment. Among those who received treatment, the vaccine was the most indicated. The pre-exposure schedule was notified in 22.94% of the cases. The largest type of exposure was biting, representing 94.58% of notifications, and the location of injuries on the lower limbs with 51.62%, followed by injuries on the hands and feet at 28.13%. Regarding the indicated treatment, among exposures by indirect contact, there was a prophylactic conduct considered inadequate (excessive). And those exposures due to minor accidents with domestic animals and involving wild animals were considered adequate, but there were some inadequacies that were considered insufficient in prophylactic conducts, such as serious accidents involving domestic animals: suspected of rabies and rabid, missing and dead. Those who interrupted any type of indicated treatment totaled 131 (2.38%) notifications, and in 85 (64.89%) cases the reason was abandonment, with an active search for the health unit in 74 (92.50% ) of these cases. There was no association between epidemiological variables and treatment discontinuation due to noncompliance.